Emerging Markets : Prospects and Challenges - Gudmundsson, Tryggvi (IMF Working Papers; Working Paper ;, 2022)
This article documents recent developments in emerging markets in the context of the COVID-19 pandemic, assesses their prospects and challenges, and discusses appropriate policy settings for the medium term. It argues that EM policymakers' ability to grapple with an incomplete and uneven recovery will be constrained by high public debt and uncertain inflation prospects as well as external risks surrounding capital flows and exchange rate developments. The paper also discusses potential impact of a tightening in global financial conditions and appreciation of the US dollar that could be triggered by a general increase in risk aversion or a reassessment of the likely path of US monetary policy.